KRITIK TERHADAP KOMPILASI HUKUM ISLAM TENTANG KETENTUAN HARTA BERSAMA DALAM PERKAWINAN - Elimartati Elimartati; Elfia Elfia (Institut Agama Islam Negeri Batusangkar, 2020)
The development and social change of the community gives impact to the regulation of the collective assets of marriage. This paper will analyse the State Act of No.1 year 1974 the 35th Article and the compilation of Islamic law (KHI) especially the Article of 1f stating about the definition of the collective asset. This research is a normative law research. It used qualitative approach. Data was analysed through content analysis. Some of the finding shows that personal property and asset becomes the collective asset caused by the marital status. Actually this changing should be stated and witnessed by the penghulu who committed the couple at the beginning of the marriage. The purpose is to avoid illegal changing of the property or asset. The regulation in Indonesia has not yet organized this case as well as possible. It must be reformulated again. Colletive asset causes the changing of responsibility to a husband in giving money to live his wife. In KHI especially in Article 80 described about the the property and asset which can be used to making a living; they are personal asset and or shared asset gathering along the marriage.